The Effect of Insecticide Resistance on Malaria Vector Control in Chikwawa, Southern Malawi - Kumala, justin (University of the Witwatersrand, Johannesburg, 2024)
Insecticide resistance poses a significant threat to malaria vector control measures, compromising the efficacy of interventions such as indoor residual spraying and insecticide-treated nets. This cross-sectional study investigated the impact of insecticide resistance on vector control tools and explored the association between resistance and mosquito plasmodium infectivity rates. CDC bottle and WHO tube assays were used to detect phenotypic resistance in wild- collected non-blood-fed female An. funestus, a key vector in the region. Circumsporozoite ELISA tests were used to detect sporozoite positivity following bioassays. The Chi-square test of independence was used to investigate the relationship between bioassay mortality and sporozoite infection rates to estimate the entomological impact of resistance. Furthermore, selected long-lasting insecticidal net (LLIN) brands, Royal Sentry and Yorkool nets, were tested for their effect on a series of wild-collected and laboratory mosquito strains with variable levels of insecticide resistance. Wash resistance tests of the selected LLINs followed a WHO protocol. The study revealed an escalation of resistance among wild An. funestus to pyrethroids. There was high resistance intensity against alpha-cypermethrin and moderate resistance to deltamethrin and permethrin. However, there was complete susceptibility to DDT and pirimiphos methyl, an organophosphate. The overall sporozoite positivity rate for An. funestus was 11.5% (n=400), highlighting high transmission in the population. The Chi-square test of independence found a significant relationship between bioassay mortality and sporozoite infection (X2 (1, N=157) = 6.889, p= 0.009). Comparatively, Royal Sentry nets exhibited higher v mortality rates (100%) for susceptible An. gambiae s.s Kisumu than Yorkool nets (69.4%). Additionally, Royal Sentry nets had better mortality rates on wild pyrethroid- resistant An. funestus (74.04%) than Yorkool nets (7.80%). Both LLINs demonstrated better efficacy in wash resistance tests on susceptible strains, especially at baseline. However, a notable decrease in efficacy was observed against the resistance mosquito strains, suggesting the potential impact of resistance on net efficacy. While these findings showed no evidence that insecticide resistance might compromise our efforts to control transmission, they highlighted the potential entomological impact of resistance. The findings also highlighted the importance of evidence-based decision-making in prioritising interventions that are effective against resistant populations. Thus, they emphasised the importance of tailoring intervention choices based on local insecticide resistance profiles.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Insecticide resistance; Malaria transmission; Long-lasting insecticide-treated net; Anopheles funestus; Wash resistance; SDG-3: Good health and well-being